FICOFLÓRULA PERIFÍTICA E PLANCTÔNICA (EXCETO Bacillariophyceae) DO BANHADO DO MATO DOS SILVA, CHIAPETTA, RS, BRASIL - Escaio, Ana C.; Corrêa, Geodeli A. P.; H., Mara L. T. (Salão do Conhecimento, 2013)
Resumo